THE EFFECTS OF ELSA SPEAK AND MOTIVATION ON SEGMENTAL AND SUPRASEGMENTAL PRONUNCIATION - Ratna Gea; Christina Natali Saragi (Jurnal Suluh Pendidikan, 2026)
This study examines the effects of the ELSA Speak application and learning motivation on students’ segmental and suprasegmental pronunciation in an EFL context in Indonesia. While mobile-assisted language learning has been widely explored, limited studies have investigated the combined role of digital tools and learner motivation in improving specific pronunciation features. This study employed a quasi-experimental design involving an experimental and a control group with 45 junior high school students. The experimental group used ELSA Speak, while the control group received conventional instruction. Data were collected through pronunciation tests and a motivation questionnaire and analyzed using t-tests and multiple regression. The findings demonstrate that ELSA Speak substantially enhances students’ pronunciation, particularly in segmental and suprasegmental aspects. Learning motivation also emerged as a strong predictor of pronunciation improvement, indicating that higher motivation leads to better performance. These results underscore the importance of integrating technology with motivational support in pronunciation instruction. This study contributes to technology-assisted language learning and provides practical insights for English teachers. However, the relatively small sample and non-random sampling limit the generalizability of the findings.